2020
DOI: 10.1002/lipd.12254
|View full text |Cite
|
Sign up to set email alerts
|

Low‐Density Lipoproteins, High‐Density Lipoproteins (HDL), and HDL‐Associated Proteins Differentially Modulate Chronic Myelogenous Leukemia Cell Viability

Abstract: Cellular lipid metabolism, lipoprotein interactions, and liver X receptor (LXR) activation have been implicated in the pathophysiology and treatment of cancer, although findings vary across cancer models and by lipoprotein profiles. In this study, we investigated the effects of human-derived low-density lipoproteins (LDL), highdensity lipoproteins (HDL), and HDL-associated proteins apolipoprotein A1 (apoA1) and serum amyloid A (SAA) on markers of viability, cholesterol flux, and differentiation in K562 cells-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 54 publications
1
2
0
Order By: Relevance
“…Further, PI helped to improve detrimental changes in intestinal immune markers but did not fully restore altered microbiome profiles associated with HCC and high-fat feeding. These findings are in line with other studies that highlight the importance of the lipid-immune relationship in cancer pathophysiology [ 8 , 9 ], and provide evidence that diet and non-lipid food components may be used as therapeutic tools in targeting endogenous lipid metabolism to improve immune outcomes within the context of chronic disease.…”
supporting
confidence: 90%
“…Further, PI helped to improve detrimental changes in intestinal immune markers but did not fully restore altered microbiome profiles associated with HCC and high-fat feeding. These findings are in line with other studies that highlight the importance of the lipid-immune relationship in cancer pathophysiology [ 8 , 9 ], and provide evidence that diet and non-lipid food components may be used as therapeutic tools in targeting endogenous lipid metabolism to improve immune outcomes within the context of chronic disease.…”
supporting
confidence: 90%
“…Metabolism-related genes, processes, and metabolites have essential roles in cancer development and progression [ 8 , 9 ]. Abnormal lipid metabolism has a significant association with the progression of hematological and other malignancies [ 10 , 11 , 18 24 ]. Furthermore, statins have demonstrated synergistic antitumor effects in vitro and have improved the survival of patients with several types of cancer, such as DLBCL, bladder cancer, breast cancer, lung cancer, adrenocortical cancer, and T-lymphoma [ 25 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…This result differed from our finding, probably because fatty acid metabolism varies according to age, and the age range of the normal population in our study (14–86 years) differed from that in the study by Zhang et al (18–65 years). Abnormal serum FFA levels were usually found in patients with metabolic diseases, such as diabetes and hyperthyroidism, and more recently, in association with some malignancies [ 10 , 11 , 18 24 ]. Studies that have uncovered the relationship between FFAs and cancer also identified the cut-off value of serum FFAs according to cancer diagnosis [ 12 , 13 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Beyond the potential direct role of egg-derived nutrients on metabolic and hematologic outcome measures, we hypothesized that variable changes in immune and erythrocyte parameters across participants may additionally be a result of improved metabolic profilesspecifically the changes in the concentration of large HDL particles, as HDL has been shown to influence immune cell activation, differentiation, and erythrocyte lifespan [52][53][54][55]. In conducting statistical correlation analysis, we found that changes in specific serum lipid and lipoprotein subclasses differentially correlated with changes in total white blood cell, neutrophil, lymphocyte, and monocyte counts between egg white and whole egg diet periods (Figure 6).…”
Section: Egg-induced Changes In Lipoprotein and Glucose Sensitivity M...mentioning
confidence: 99%